2023
DOI: 10.7717/peerj.14789
|View full text |Cite
|
Sign up to set email alerts
|

The contents of essential and toxic metals in coffee beans and soil in Dale Woreda, Sidama Regional State, Southern Ethiopia

Abstract: Background For developing countries such as Ethiopia, coffee is a commodity of great economic, social, and environmental importance. No detailed investigations have been performed on the contents of essential and toxic metals in coffee beans and soil in this study area. Methods The levels of essential metals (Na, K, Ca, Zn, Mn, Cu, Co, Cr, Ni) and toxic elements (Pb and Cd) were investigated in coffee beans (coffee growing farmland and coff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
2
1
Order By: Relevance
“…Cu content is probably slightly higher in Arabica than in Robusta beans. Berego et al [ 34 ] did not detect Pb or Cd in samples of green coffee beans from Ethiopia, in contrast to our findings.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Cu content is probably slightly higher in Arabica than in Robusta beans. Berego et al [ 34 ] did not detect Pb or Cd in samples of green coffee beans from Ethiopia, in contrast to our findings.…”
Section: Discussioncontrasting
confidence: 99%
“…The Ni contents of the green coffees in our study differed depending on the processing method, especially in ETH-Gedeo (washed vs natural), KEN (washed vs natural), NIC (washed vs honey), and PER (natural vs anaerobic fermentation), consistent with the Ni contents for the Columbian fermented and NIC natural green coffees [ 18 ]. Berego et al [ 34 ], however, found much lower Ni contents (0.052–0.074 mg/kg) in washed and natural green coffees from Ethiopia. Ni content in our study, however, was significantly higher in roasted coffees, mainly in fermented coffee (ETH [ACR], RWA [60-h fermentation], and GUA [AFH]), but also in washed coffee (KEN).…”
Section: Discussionmentioning
confidence: 99%
“…The iAs concentration ranged between the LOD and 0.1 mg/kg[6,46,47]. Cr was not detected in the studies such as those byBerego et al (2023) [48]; Getachew and Worku (2014) [49]; Şemen et al (2017) [6]. Values around E-03 mg/kg were reported by Dubale et al (2017) [50] in Ethiopian coffees and Rodrígues et al (2011) [51] in Hawaiian beans.…”
mentioning
confidence: 87%